Stellar flares and the dark energy of CMEs. Issue Volume 11:Issue S320(2015) (9th September 2016) - Drake, Jeremy J.; Cohen, Ofer; Garraffo, Cecilia; Kashyap, V.
Abstract: Flares we observe on stars in white light, UV or soft X-rays are probably harbingers of coronal mass ejections (CMEs). If we use the Sun as a guide, large stellar flares will dissipate two orders of magnitude less X-ray radiative energy than the kinetic energy in the associated CME. Since coronal emission on active stars appears to be dominated by flare activity, CMEs pose a quandary for understanding the fraction of their energy budget stars can spend on magnetic activity. One answer is magnetic suppression of CMEs, in which the strong large-scale fields of active stars entrap and prevent CMEs unless their free energy exceeds a critical value. The CME-less flaring active region NOAA 2192 presents a possible solar analogue of this. Monster CMEs will still exist, and have the potential to ravage planetary atmospheres.